Recursive Digital Filters With Predetermined Group Delay And Chebyshev Stopband Attenuation - Thajchayapong, P.; Yammun, K.; Khunkitti, A. (My University, 1988)
Recently, a conformal mapping technique has been described whereby the transfer function of a recursive digital filter with prescribed group delay and Chebyshev stopband can be obtained in such a way that the numerator and denominator polynomials are different in order. It is shown here that such a transfer function can also be determined using the familiar bilinear transformation and the well known method in the s-domain. Numerical examples are included to demonstrate the technique. © 1988, The Institution of Electrical Engineers. All rights reserved.
Keywords: Digital filters; Filters; Transfer functions